Rapid diagnosis of trisomy 21 by relative gene copy using real-time quantitative polymerase chain reaction - Sanguansermsri,C. (IOS Press, 2015)
Background: Trisomy 21 or Down syndrome (DS) is the most common aneuploidy disorder. Fetal karyotypic analysis remains the criterion standard for prenatal diagnosis of DS, although the method is time consuming and requires skilled personnel. Real-time quantitative polymerase chain reaction (qPCR) can be used to determine a difference in the amount of gene copy by calculation of the difference between the cycle threshold (ΔCT) of a tested gene and a reference gene. Objectives: To develop a rapid qPCR diagnostic method for trisomy 21. Methods: Ten DS patients with the known karyotype of trisomy 21 were enrolled. Their parents were included as controls. D21S11 locus on chromosome 21 and SM locus on chromosome 16 from each subject were amplified by qPCR. The D21S11/SM ΔCT and 2-ΔΔCT values were compared between DS patients and their parents. Results: The D21S11/SM ΔCT values of the DS patients were higher than their respective controls except for one family. The mean 2-ΔΔCT value between patients and mothers was 1.88 ± 0.95 (95% CI 1.20-2.56), and between fathers and mothers as controls was 1.06 ± 0.68 (95% CI 0.58-1.54). Conclusion: The diagnostic method of trisomy 21 by using qPCR is feasible, although false negative results may occur. Using more index genes is recommended to increase the sensitivity and specificity.